Models to predict disease‐free survival for hepatocellular carcinoma patients with surgical resections. Issue 7 (1st September 2020) - Lai, Yin; Lee, Jin‐Chiao; Hung, Hao‐Chien; Cheng, Chih‐Hsien; Wu, Tsung‐Han; Lee, Chen‐Fang; Wu, Ting‐Jung; Chou, Hong‐Shiue; Chan, Kun‐Ming; Lee, Wei‐Chen
Abstract: Background and Objectives: Precise prognostic prediction for an individual hepatocellular carcinoma (HCC) patient before and after liver resection is important. We aimed to establish simple prognostic models to predict disease‐free survival (DFS) for these patients. Methods: Six hundred and ninety‐eight HCC patients with liver resections were reviewed. Preoperative (model 1) and postoperative (model 2) nomogram‐based scoring systems were constructed by multivariate analyses, and DFS was estimated. Results: Among 698 patients, 490 (70.2%) patients had tumor recurrence at a median follow‐up of 84.4 months. Risk factors of tumor recurrence in model 1 included viral hepatitis, platelet count, albumin, indocyanine green retention rate, multiplicity of tumor, and radiologic total tumor volume (TTV). Prognostic variables identified in model 2 were viral hepatitis, platelet count, multiplicity of tumor, cirrhosis, microvascular invasion, and pathologic TTV. By nomogram in model 1, the patients were classified into three groups with 5‐year DFS of 61.0%, 35.7%, and 21.1%, respectively ( P < .0001). In model 2, the patients were divided into five groups with 5‐year DFS of 58.0%, 43.7%, 24.0%, 15.4%, and 0.0%, respectively ( P < .0001). Conclusion: Based on nomogram models, DFS for the patients who had liver resection for HCC can be predicted before liver resection and re‐assessed after liver resection.